Tele-Coaching Korean Parents for Improving Occupational Performance of Toddlers: Three Case Reports - Dabin Choi; Aeri Yu; Misun Kim; Eun Young Kim (MDPI AG, 2023)
Telehealth has been applied to occupational therapy practice since the COVID-19 pandemic, but no research has been conducted on the use of telehealth to improve the occupational performances of Korean children and parents. This study explored the possibility of tele-coaching parents to improve toddlers' occupational performance and parenting competence in Korea. Three mothers of toddlers received Occupational Performance Coaching (OPC) via videoconference. The Canadian Occupational Performance Measure (COPM) and the Parenting Sense of Competence Scale (PSOC) were used pre- and post-intervention to measure the occupational performances of the toddlers and parents and parenting competence. Post-intervention interviews were conducted to explore the parents' experiences with the tele-coaching and analyzed by content analysis. Most of the COPM scores showed a significant increase. The PSOC scores also increased. The mothers reported their learning, the changes in their children, the appropriateness of the coaching, and the usefulness of the tele-coaching delivery. The findings demonstrate the potential of tele-coaching as a practical intervention for Korean children and parents.